Effects of TLR3 and TLR9 Signaling Pathway on Brain Protection in Rats Undergoing Sevoflurane Pretreatment during Cardiopulmonary Bypass. (27th December 2017) - Nan, Zhou; Jin, Zhou; Huijuan, Cao; Tiezheng, Zhang; Keyan, Chen
Abstract : Objective . To investigate the effects of TLR3 and TLR9 signaling pathway on brain injury during CPB in rats pretreated with sevoflurane and its possible molecular mechanism. Methods . SD rats were randomly assigned to sham group, CPB group, and Sev group. Brain tissue was obtained at before CPB (T 0 ), at CPB for 30 minutes (T 1 ), 1 hour after CPB (T 3 ), and 3 hours after CPB (T 5 ). ELISA was used to measure S100- β and IL-6. Western blot was utilized to determine TLR3 and TLR9 expression. TUNEL was applied to detect neuronal apoptosis. Results . Compared with CPB group, at T 1, at termination after 1 hour of CPB (T 2 ), T 3, 2 hours after CPB (T 4 ) and T 5, S100- β and IL-6 decreased in Sev group. Compared with CPB group, IFN- β were increased in Sev group, except T 0 . Compared with CPB group, TLR3 expression increased, and TLR9 and NF- κ B decreased in Sev group. The apoptotic neurons were less in Sev group than in CPB group (P < 0.05 ). Conclusion . Sevoflurane intervention can activate TLR3 and TLR9 signaling pathway, upregulate TLR3 expression and downstream TRIF expression, decrease TLR9 expression, and downregulate downstream NF- κ B expression in CPB rat models, thereby mitigating brain injury induced by inflammatory response during CPB.